2018
DOI: 10.3892/ol.2018.9505
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of CADM1 and MAL together with HPV status in cytological cervical specimens serves an important role in the progression of cervical intraepithelial neoplasia

Abstract: Cervical cancer (CC) is the second most common type of cancer affecting the female population. The development of CC takes several years, and involves a precancerous stage known as cervical intraepithelial neoplasia (CIN). A key factor in the development of disease is the human papillomavirus (HPV) infection, which initiates carcinogenesis. Furthermore, CC is also impacted by epigenetic changes such as DNA methylation, which causes activation or exclusion of certain genes, and the hypermethylation of cytosines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…It is the same as to cervical cancer. Downregulated CADM1, caused by its promoter hypermethylation, was involved in the metastasis and prognosis in CC patients . However, to the best of our knowledge rare studies have investigated CADM1 promoter hypermethylation from blood samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is the same as to cervical cancer. Downregulated CADM1, caused by its promoter hypermethylation, was involved in the metastasis and prognosis in CC patients . However, to the best of our knowledge rare studies have investigated CADM1 promoter hypermethylation from blood samples.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulated CADM1, caused by its promoter hypermethylation, was involved in the metastasis and prognosis in CC patients. [28][29][30] However, to the best of our knowledge rare studies have investigated CADM1 promoter hypermethylation from blood samples. Therefore, we firstly showed the high coincidence rate of CADM1 promoter methylation in pair-matched tissue and plasma samples of CC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important that the sensitivity, specificity, and rate of methylation of all the biomarkers are similar ( Table 2). Mersakova et al (2018) and Rong et al (2019) have recently shown that CADM1 is a potential biomarker for cervical cancer. There was a significant difference in the promoter Kan et al, 2014;Lai et al, 2014;Kong et al, 2015;Nikolaidis et al, 2015;Xu et al, 2015Xu et al, , 2018Chen et al, 2016;Liou et al, 2016;Huang et al, 2017;Fang et al, Lee et al, 2006;Yeon et al, 2018 methylation of plasma CADM1 and its D-dimer between healthy individuals and those with cervical cancer.…”
Section: Dna Methylation In the Early Diagnosis Of Cervical Cancermentioning
confidence: 99%
“…Therefore, DNA methylation may be used as a marker in early cancer screening (24,(42)(43)(44). Hypermethylation of specific TSG, as well as low mRNA and protein expression levels, has been reported in a number of human malignancies, including EC (28,45,46). HOXD10 is one of the ANTP homeobox genes located on chromosome 2 (2p31).…”
Section: Discussionmentioning
confidence: 99%